Anti-heroes of the Canadian Expeditionary Force - Cook, Tim (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractThe civilian-soldiers that formed the ranks of the Canadian Corps created a unique soldiers’ culture composed of songs, poetry, doggerel, cartoons, and newspapers during the course of the war to cope with the strain of service. This unique soldiers’ culture offers keen insight into soldiers’ experience. The antihero was one of the most important themes running through soldiers’ culture. In a war where soldiers were elevated to heroes by civilians, the soldiers in turn often chose instead to emphasis the antiheroic in their cultural products. There were several antihero archetypes in Canadian soldiers’ culture, and this essay will examine three: British cartoonist Bruce Bairnsfather’s Old Bill, “old soldiers,” and malingers. While these archetypes were separate, with identifiable qualities, they also bled into one another, creating a rich tapestry of anti-heroic cultural products and icons. These antiheroes provided a voice to the soldiers, even at times a language by which the soldiers could make sense of their war experience. The antiheroes were not always emulated, but their unheroic actions resonated with the trench warriors.